Developing Strategy: A Guide For Nurse Managers to Manage Nursing Staff's Work-related Problems - Amal Refaat Gab Allah; Hayam Ahmed Elshrief; Marwa Hassan Ageiz (Asian Nursing Research, 2020)
Summary: Purpose: The purpose of this study was to assess nursing staff's work-related problems as perceived by their managers and thereafter develop strategies that would serve as a guide for nurse managers to manage these problems. Methods: A descriptive research design was used. The participants included in the study consisted of the following two groups: Group 1—a convenience sample of 150 first-line managers working at three different hospitals; and Group 2—a panel of experts for the Delphi technique, selected using the Snowball sampling technique. Tools for data collection included the following: Tool 1—questionnaire about nursing staff's problems; Tool 2—Delphi technique to develop strategies for managing nursing staff's problems; and Tool 3—opinionnaire format. Results: The recruited first nurse managers were of the opinion that job stress, work overload, conflict, workplace violence, poor performance, staff turnover, demotivation, lack of empowerment, and staff absenteeism were among the common problems faced by staff nurses at work. Conclusion: From the expert panelists’ perspectives, the newly developed strategy in this study was considered valid; the researchers recommend the strategy developed in this study to be universalized in different health care settings and used as a guide for nurse managers.